Мозковий інсульт: медична реабілітація і механізми саногенеза – основні поняття і дефініції = Cerebral stroke: medical rehabilitation and mechanisms of sanogenesis – basic concepts and definitions - Samosyuk, I. Z.; Samosyuk, N. I.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Samosyuk I. Z., Samosyuk N. I., Zukow W. Мозковий інсульт: медична реабілітація і механізми саногенеза – основні поняття і дефініції = Cerebral stroke: medical rehabilitation and mechanisms of sanogenesis – basic concepts and definitions. Journal of Education, Health and Sport. 2015;5(1):100-116. ISSN 2391-8306. DOI: 10.13140/2.1.1414.1763 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A100-116 https://pbn.nauka.gov.pl/works/529087 http://dx.doi.org/10.13140/2.1.1414.1763 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2014. Revised 18.01.2015. Accepted: 20.01.2015. Мозковий інсульт: медична реабілітація і механізми саногенеза – основні поняття і дефініції Cerebral stroke: medical rehabilitation and mechanisms of sanogenesis – basic concepts and definitions Samosyuk I. Z., Samosyuk N. I., Zukow W. Самосюк І.З., Самосюк Н.І., Жуков В.А. National Medical Academy of postgraduate education named after P.L. Shupyk, Kyiv, Ukraine Kazimierz Wielki University, Bydgoszcz, Poland Національна медична академія післядипломної освіти імені П.Л. Шупика, Kyiv, Ukraine Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska Ключові слова: інсульт, саногенез, медична реабілітація. Key words: stroke, sanogenesis, medical rehabilitation. Резюме Наводяться основні компоненти саногенетичних процесів, при стимуляції яких можна впливати на підвищення результатів медичної реабілітації післяінсультних хворих. Звертається увага лікарів на необхідність засвоєння питань реабілітаційної медицини в сучасній інсультології. Abstract We give components sanogenetic processes, the stimulation of which can affect the medical rehabilitation after the stroke patients. Attention physicians on the necessity of learning matters rehabilitation medicine in modern insultology.